One Bite or Two? A Prospective Trial Comparing Colonoscopy Biopsy Technique in Patients with Chronic Ulcerative Colitis - Lawrence C Hookey; David J Hurlbut; Andrew G Day; Paul N Manley; William T Depew (Canadian Journal of Gastroenterology)
BACKGROUND AND STUDY AIMS: Surveillance for mucosal dysplasia in patients with chronic ulcerative colitis requires numerous biopsies (often over 40). The aim of the present study was to determine if two biopsies could be obtained with jumbo forceps before removing them from the instrument (double biopsy technique), as opposed to one biopsy per pass, without sacrificing the histological quality of the biopsy material.